Insight into molecular and mutational scrutiny of epilepsy associated gene Gabrg2 leading to novel computer-aided drug designing - Muhammad Naveed; Nimra Hanif; Tariq Aziz; Muhammad Waseem; Metab Alharbi; Abdulrahman Alshammari; Abdullah F. Alasmari (Scientific Reports)
Abstract Epilepsy is a neurological disorder that is major cause of disability in the world. This is most severe medical condition related with different ion channel genes, inflammatory molecules depression and stress. For this purpose, precise diagnostic techniques are available. Genetic polymorphisms are major factors behind the occurrence of many disorders therefore they can be valid for diagnostic purpose. This study emphasis the finding of such markers in Lahore population. Epilepsy-causing gene GABRG2 was selected, and the gene was then examined to detect the presence of polymorphic markers with the help of molecular (PCR) and computational analysis. 50 blood samples of epilepsy patients were collected from Children hospital Lahore, out of which 2 samples were shown positive response for GABRG2 gene, indicating that this gene is becoming the cause of seizures in epilepsy patients. These samples underwent mutational screening, which revealed 6 new mutations in exon 3 region of these samples as a result of disease occurrence. There are no proper treatments of epilepsy offered despite the development of anti-leptic and anti-seizure drugs. To solve this issue, researchers are working to create innovative methods of treating epilepsy, that incorporate the use of herbal remedies. 31 plant compounds have been used in this study but only one compound cyanidin was selected on the base of best binding affinity. Moreover, SwissAdme, QSAR analysis and molecular simulations demonstrated that cyanidin is a best natural drug model which have best responses as compared to other epileptic drugs and can be tested for future application in laboratories.